Evaluation of antidepressant properties of the p38 MAP kinase inhibitor losmapimod (GW856553) in Major Depressive Disorder: Results from two randomised, placebo-controlled, double-blind, multicentre studies using a Bayesian approach. (June 2014) - Inamdar, Amir; Merlo-Pich, Emilio; Gee, Michelle; Makumi, Clare; Mistry, Prafull; Robertson, Jon; Steinberg, Erik; Zamuner, Stefano; Learned, Susan; Alexander, Robert; Ratti, Emiliangelo
Pro-inflammatory cytokines (PICs) may play important pathophysiological roles in some forms of Major Depressive Disorder (MDD). The p38 MAPK inhibitor losmapimod (GW856553) attenuates the pro-inflammatory response in humans by reducing PIC production. Losmapimod (7.5 mg BD) was administered for 6 weeks in two randomised, placebo-controlled trials in subjects with MDD enriched with symptoms of loss of energy/interest and psychomotor retardation (Studies 574 and 009). Primary efficacy endpoints were the Bech 6-item depression subscale of the HAMD-17 (the 'Bech, ') for Study 009; and the Bech, Inventory of Depressive Symptomatology-Clinician Rated (IDS-C), HAMD-17, and Quick Inventory of Depressive Symptomatology (self-rated) (QIDS-SR) for Study 574. Key cytokine biomarker levels were also measured. Study 574 ( n =24) was terminated prematurely in light of emerging data from an internal study in rheumatoid arthritis. Efficacy results available at termination favoured losmapimod (Bech, 6 weeks: endpoint drug vs. placebo difference = −4.10; 95% CI, −7.36, −0.83; p =0.017). A subsequent study, Study 009 ( n =128), designed using a Bayesian approach based on a prior derived from Study 574, showed no advantage for losmapimod (Bech, 6 weeks: endpoint drug vs. placebo difference = 1.11; 95% credible interval, −0.22, 2.50). Biomarker data showed no significant changes. In conclusion 7.5 mg BID losmapimod was not effective in MDD.